FTAs and the crisis in the European car industry: A free trade position on the car crisis and the Economic Integration Agreement (EU-Japan FTA) - Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2012)
The crisis-struck EU finds it increasingly difficult to engage in trade negotiations with large-sized economies that would have a meaningful impact on growth. Some parts of the European car industry are opposing a FTA with Japan due to defensive interests following the crisis in EU car manufacturing. But such a position is misguided: The crisis in the car industry has its roots in long-term decline in innovation, competitiveness and focus on low-profit segments. The crisis was neither caused or worsened by foreign imports, whose drop in sales was disproportionate to cars made in the EU. State interventions and subsidies were also counterproductive, and the value-added in some EU Member States are now lagging behind countries like Brazil. These developments have practically split the European car industry into two - while the majority are competitive and successful exporters, a small part (representing less than 0.3% of the economic value-added in the EU) is affected by permanent overcapacities. Meanwhile, benefits from market access to large-sized economies, export efficiencies, technology and supply chain improvements, all contribute towards revitalising growth in EU car manufacturing, as well as other sectors.
Keywords: 330; Freihandelszone; Kfz-Industrie; EU-Staaten; Japan